Studi Penjaminan Mutu (Quality Assurance) Internal Dalam Pelayanan Kefarmasian - Madania Madania; Faramita Hiola; Rahmawati Marjun; A. Mu’thi Andy Suryadi (State University of Gorontalo, 2023)
Pharmaceutical services in hospitals aim to improve the quality of pharmaceutical services, protect patients from irrational drug use to maintain patient safety, and ensure legal certainty for pharmacists. Quality Assurance (QA) is used in measuring service quality, whereas QA in IFRS aims to provide assurance of product quality and the quality of pharmaceutical services provided to patients. This research employs descriptive research with a cross-sectional method, and primary date are obtained from questionnaires with the framework of QA standard indicators in pharmaceutical services at the primary Installastion of Mother and Child Hospital Kasih Fatimah Kotamobagu, with five respondents. The results indicate that internal quality assurance in pharmaceutical services at the Fatimah Kotamobagu Mother and Child Hospital Kasih Fatimah Kotamobagu Pharmacy Installation was in accordance with quality assurance standards, especially in the aspects of organizational structure, quality measures, and safety assurance, as well as drug distribution with an overall value in the criteria, are (75%), moderately appropriate are (15%) and not appropriate are (10%).